PRODUCTION OF POLYUNSATURATED FATTY ACIDS BY FUNGI: A REVIEW - ANANIA ARJUNA, (International Journal of Pharma and Bio Sciences, 2014)
Omega (w)-6 PUFAs, or especially gamma linolenic acid (cis, cis, cis 6,9,12 octadecatrienoic acid) comprised of 18 carbon atoms and three double bonds is also known as gamolenic acid. Gamma Linolenic Acid (GLA) is found naturally in varying extends in the fatty acid fraction of some plant seed oil. Recent research suggests that gamma (γ) -linolenic acid is unique among the n-6 polyunsaturated fatty acid (PUFA) family members as it ameliorates many health problems. There are many evidences suggesting GLA for pharmacological and dietetic purposes. Over the past several years’ extensive research has been made for the microbial production of PUFA. The focus has been laid down to maximize PUFA yield by novel mutations, genetic manipulations, isolating new strains as well as optimizing the media for cultivating more efficient strains. The aim of this work was to isolate and screen GLA-producing filamentous fungi and to optimize various process parameters for GLA production through systematic manipulation of the fermentation parameters. The thesis also aims at inhibiting the genes responsible for further elongation of the carbon chain in the biosynthetic pathway of this fungus. The ultimate objective of the study is to develop new edible oil based, value-added products by using an optimal source of omega 6 polyunsaturated fatty acids specifically GLA.